Improvements and future challenges for the research infrastructure in the field firm level data - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
This paper discusses issues related to the use of confidential firm level data in Germany. It starts by defining firm level data (in section 1) and reminding us what they are good for (in section 2), who produces firm level data in Germany, and how researchers can access these data today (in section 3). In section 4, new and ongoing developments are discussed that are leading to new products new types of firm level data that will enhance the research potential available to researchers considerably in the near future. Section 5 concludes with a wish-list.
Keywords: 330; Statistik der Unternehmen und Arbeitsstätten; Mikrodaten; Panel; Wirtschaftsforschung; Deutschland